The Intention to Repeat Visit Tourist on the Geotourism Object of Cave Bentar, Tanjungsari, Yogyakarta - RAHATMAWATI, Istiana; BAHAGIARTI, Sari; PRASTISTHO, Bambang; SETYANINGRUM, Tuti; ZAKARIA, Muhammad Faizal; PRIYANDHITA, Nadia (Journal of Environmental Management and Tourism; Vol 11 No 8 (2020): JEMT Volume XI Issue 8(48) Winter 2020, 2020)
This study aims to determine the effect of motivation, experience, attractiveness, and reputation on the intention to return visits tourists to the Cave Bentar geotourism object, Hargosari Village, Tanjungsari District, Gunungkidul Regency, Yogyakarta Special Region, Indonesia in 2020. This research was conducted on Cave Bentar geotourism tourists. The variables used in this study were independent variables consisting of motivation, experience, attractiveness, and reputation. Meanwhile, the dependent variable in this study is the intention of returning tourists. This research includes in a survey type, using partial least square analysis. The sampling method used in this study was convenience sampling. The results of this study indicate that (1) motivation, experience, attractiveness, and reputation have a positive and significant effect simultaneously on the intention of returning tourists to the object of Bentar Cave Geotourism. (2) motivation, experience, attractiveness, and reputation have a positive and significant effect partially on the intention of returning tourists to the object of Bentar Cave Geotourism.